2022
DOI: 10.1007/s13304-022-01244-2
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical complications after robot-assisted transaxillary thyroidectomy: critical analysis of a large cohort of European patients

Abstract: In the last decade, robot-assisted trans-axillary thyroidectomy has spread rapidly and has been proven to be a safe and effective procedure. However, several case series have reported new complications that have led to criticism regarding this approach. This study analyzed the incidence of complications in a large cohort of European patients. We enrolled all patients who underwent robot-assisted trans-axillary thyroidectomy from 2012 to 2020 at the University Hospital of Pisa Department of Endocrine Surgery. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…The Authors reported that it has never account for more than 1% of thyroid surgeries per year and that the majority of procedures were performed by low-volume institutions, although these were associated to a significant higher rate of surgical complications compared to high-volume ones (p = 0.02) [5]. Moreover, the introduction on novel complications [14] and prohibitive costs hinder the diffusion of RATT in the Western World and several Authors heavily criticized this new approach [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Authors reported that it has never account for more than 1% of thyroid surgeries per year and that the majority of procedures were performed by low-volume institutions, although these were associated to a significant higher rate of surgical complications compared to high-volume ones (p = 0.02) [5]. Moreover, the introduction on novel complications [14] and prohibitive costs hinder the diffusion of RATT in the Western World and several Authors heavily criticized this new approach [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Although anthropometrics' and thyroid's features of European patients are similar to those of Americans, in Europe some high-volume institutions perform RATT routinary reporting case series of hundreds of patients [14,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroidectomy is the most frequently performed surgical procedure in endocrine surgery, for the treatment of both benign diseases and malignancy (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Neuropraxia of the brachial plexus is thought to result from extreme arm extension and surgical flap retraction [25]. The incidence of brachial plexus injury is reported at 0.2-2.2% [24,26,27]. Fortunately, brachial plexus injury caused by RATS is generally transient as it is due to neuropraxia and improves over time (in contrast to nerve transection) [28,29].…”
Section: Surgerymentioning
confidence: 99%